2006
DOI: 10.1111/j.1365-2028.2006.00632.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil quality around a solid waste dumpsite in Port Harcourt, Nigeria

Abstract: The levels of soil parameters and selected heavy metals around a solid waste dumpsite receiving untreated wastes from all sources and a control site within Port Harcourt, Nigeria have been examined. Top soil (0-15 cm) and sediment samples were collected and analysed for pH value, particle size, total nitrogen, potassium, available phosphorus, organic matter, effective cation exchange capacity, cadmium, nickel and lead using standard methods. The results showed that the waste dump contributed to the high levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 6 publications
3
12
0
Order By: Relevance
“…This is in agreement with the results obtained from similar studied by [13]. [35], also reported higher levels of some heavy metals in soils around designated municipal solid waste dump site compared to the control site within Port Harcourt and its environment. As showed in (Table 2), the recorded results of accumulated heavy metals in soil showed that zinc, manganese, iron and lead has the higher value at both dumping sites relative to other heavy metals.…”
Section: ) Heavy Metals Concentration In Soilsupporting
confidence: 83%
“…This is in agreement with the results obtained from similar studied by [13]. [35], also reported higher levels of some heavy metals in soils around designated municipal solid waste dump site compared to the control site within Port Harcourt and its environment. As showed in (Table 2), the recorded results of accumulated heavy metals in soil showed that zinc, manganese, iron and lead has the higher value at both dumping sites relative to other heavy metals.…”
Section: ) Heavy Metals Concentration In Soilsupporting
confidence: 83%
“…It was observed that the soil textural class of the dump sites studied was mostly loamy sandy except for the Iwofe dump site which was sandy soil. This has also been reported in similar study that decomposition of agricultural wastes influence the texture of the soil (Ideriah et al, 2006). The mean sand percentage in the study locations for wet and dry seasons.…”
Section: Figmentioning
confidence: 51%
“…The higher pH level in the dump sites than their controls has been reported to be as a result of liming materials and also the activities of some microorganism on the solid wastes (Ayade, 2003, Ideriah et al, 2006. Furthermore, pH has been reported as a simple and direct measure of the overall chemical condition of the soil and at pH 6.5, nutrients availability to plants from the soil is at its highest (Praveena and Rao, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The soils studied are not deficient in available phosphorus because the values were generally higher than 6.0 mg/kg (Defoer et al, 2000). This may be due to the availability of high amount of organic matter and plants decomposition (Ideriah et al, 2006) and leaching off of fertilizer nutrients from agricultural farms from the surrounding communities. The high levels of Ca and Mg in the soils could be attributed to the high base saturation and pH levels of the soils studied (Middha et al, 2015).…”
Section: Adetuga At Omonona Ao; Jubril Ajmentioning
confidence: 99%